Talang Tuo inscription: The management of environmental in Sriwijaya period - Sondang M Siregar (Indonesian Journal of Environmental Management and Sustainability, 2018)
Talang Tuo inscription was an inscription which made Sriwijaya King, Dapunta Hiyam Sri Jayanasa. The inscription was found by Westenenk in 1920 at the foot of Bukit Siguntang that written in Pallawa and Malay language. The inscription contains about environmental management to prosperity of living beings. Talang Tuo inscription studies through could aware that since in the past the government had thought to maintain the natural balance between plants, animals and humans. Human beings regulate and keeping nature so that the plant can grow and fruitful experience for being well of living creatures. In addition since the time of Sriwijaya had known water management that functions to fulfillment of daily needs, means of transportation and irrigation during the Sriwijaya period.